Adjunctive Corticosteroid Therapy Decreases Lung Permeability in Patients with AIDS-Related Pneumocystis carinii Pneumonia - Silvia Guillemi; Allan Belzberg; Lindsay M Lawson; Martin T Schechter; Julio SG Montaner (Canadian Respiratory Journal)
OBJECTIVE: To assess the effect of adjunctive corticosteroid therapy on lung permeability as measured by Tc-DTPA lung clearance scan in patients with AIDS-related Pneumocystis carinii pneumonia (PCP).